Tannic acid intermediated surface functionalization of bamboo micron fibers to enhance mechanical performance of hybrid GFRP. (15th November 2019) - Singh, Ashangbam Satyavrata; Halder, Sudipta; Wang, Jialai; Imam, Muhammad A.; Chen, Peiyuan
Abstract: In this study, tannic acid (TA) mediated surface functionalization of bamboo micron fibers (BMFs) was done through a simple green process and subsequently compared with their counterpart based on silane treatment to use them as reinforcement in the hybrid laminated composite. The surface functionalized BMFs were characterized using XPS to reveal the attachment of the functional ligands. Introduction of TA-treated BMFs (TBMFs) in hybrid glass fiber reinforced plastics (GFRP) improves the σ y and E of the composite over GFRP by ~48% and ~55%, respectively. Drastic improvement in flexural properties is also observed mainly attributed to the restriction to microcracks formation and fiber debonding at the inter-ply regions of the GFRP. TA provides a green alternative surface functionalization agent for highly porous natural fibers, making them a low-cost attractive reinforcement used in high-performance hybrid GFRP. Graphical abstract: Image 1